2021
DOI: 10.1007/978-981-16-1288-6_9
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosing Parkinson’s Disease Using Multimodal Physiological Signals

Abstract: Parkinson's disease (PD) is the second most common neurodegenerative disease after Alzheimer's disease. Due to the complex etiology and diverse clinical symptoms, it's difficult to accurately diagnose PD. In this study, we applied multimodal physiological signals, which include electroencephalography (EEG), electrocardiogram (ECG), photoplethysmography (PPG), and respiratory (RA), to classify PD and healthy control (HC) based on a multimodal support vector machine (SVM). Our experiments achieved an accuracy of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 30 publications
(33 reference statements)
0
3
0
Order By: Relevance
“…It is mentioned that Huntington's disease will interfere with the recognition of negative emotions, especially anger, disgust, and fear [54]- [56]. Patients with affective decline who attack their brains best identify their emotions through physiological signals, including electroencephalography (EEG), electrocardiogram (ECG), photoplethysmography (PPG), and respiratory (RA), to classify PD and healthy control (HC) [57]. This is in line with other research that showed weaknesses in facial emotion recognition in these patients due to impairments in facial emotion mimicking [58].…”
Section: Research Topic In Multimodal Emotion Recognitionmentioning
confidence: 99%
“…It is mentioned that Huntington's disease will interfere with the recognition of negative emotions, especially anger, disgust, and fear [54]- [56]. Patients with affective decline who attack their brains best identify their emotions through physiological signals, including electroencephalography (EEG), electrocardiogram (ECG), photoplethysmography (PPG), and respiratory (RA), to classify PD and healthy control (HC) [57]. This is in line with other research that showed weaknesses in facial emotion recognition in these patients due to impairments in facial emotion mimicking [58].…”
Section: Research Topic In Multimodal Emotion Recognitionmentioning
confidence: 99%
“…Biofeedback therapy using SMR and ECG and RSP as feedback signals can effectively improve the motor symptoms of PD [26][27]39], while ECG, PPG, and RSP signals can improve nonmotor symptoms such as cognition and depression [40][41][42]. The weight parameters of EEG, ECG, PPG, and RSP signals were obtained from the research of Guo et al [43]. Brain Sci.…”
Section: Biofeedback Protocolmentioning
confidence: 99%
“…This was reflected in [65], which classified PD patients in the ON state vs. OFF state of medication, and in those studies that evaluated cognitive impairment [32,34,45,47,53]. Consequently, those articles that did not specify the clinical setting of the patients [37,40,42,43,46,51,53,55,56,[58][59][60][61][62][64][65][66][68][69][70], nor the status of the medication in the patients [32,33,35,41,50,54,63,71] were excluded from the evaluation process of the current state of diagnosis of PD, because they did not allow the objective evaluation of the results of the models used. These exclusions, based on quality criteria, resulted in 15 admissible articles.…”
Section: Quality Of the Datasetmentioning
confidence: 99%